BUDDHIST COUNSELING APPROACHES FOR ENHANCING SELF-CONFIDENCE OF GRADE 8 STUDENTS AT WAT SAENGSAN SCHOOL IN PATHUM THANI PROVINCE - Kittiyano (Nueanin), PramhaKrit; Woramongkhalo, PhrakhrupaladMarut; Vajirapañyo, PhrasamuChokdee; Mererk, Sayyud (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aims to: 1) study the level of self-confidence of Grade 8 students at Wat Saengsan School, Pathum Thani Province, and 2) study Buddhist counseling approaches to enhance self-confidence of Grade 8 students at Wat Saengsan School, Pathum Thani Province. This was a mixed-methods research. The quantitative reserach involved a survey of 100 Grade 8 students at Wat Saengsan School, conducted via questionnaires. Data were analyzed using descriptive statistics, including percentages, means, and standard deviations. The qualitative research involving interviews with 8 key informants, comprising teachers, with data analyzed using content analysis. The research findings revealed that: 1) The overall self-confidence of Grade 8 students at Wat Saengsan School, Pathum Thani Province, was at a moderate level. When ranked by dimension according to the Five Powers (Pancha-bala), the aspect at a high level was Wisdom (Paññ ), contrast, the remaining four dimensions were at a moderate level: Concentration (Sam dhi), Effort (Viriya), Mindfulness (Sati), and Faith (Saddh ) respectively. And 2) The study found Buddhist counseling approaches to enhance self-confidence of Grade 8 students at Wat Saengsan School, Pathum Thani Province comprising of five key areas: (1) Faith Strength (Saddh -bala), focuses on strengthening self-belief and helping students recognize their intrinsic self-worth, fostering trust in the counselor and the process, emphasizing encouraging communication and highlighting strengths. (2) Effort Strength (Viriya-bala): Promoting perseverance in self-development, motivating clients to be determined and not give up in the face of obstacles, helping them set goals, and monitoring progress, emphasizing concrete and continuous planning. (3) Mindfulness Strength (Sati-bala): Training self-awareness, helping clients understand their emotions, thoughts, and behaviors, using open-ended questioning techniques and reflection to promote mindful decision-making. (4) Concentration Strength (Sam dhi-bala): Strengthening mental stability through activities that promote calmness, attentive listening, and helping clients view problems systematically and avoid distractions. (5) Wisdom Strength (Paññ -bala): Promoting rational thinking, helping clients understand problems deeply, stimulating analytical thinking and exploring diverse options, emphasizing careful decision-making.